Nurses' experiences and attitudes towards family witnessed resuscitation an accident and emergency units in two South African hospitals - Motsepe, Tshepo Lillet (My University, 2016)
Background: Family witnessed resuscitation is a practise that is internationally growing and nurses’ attitudes and experiences influence this practice. Aim: To determine the experiences and attitudes of nurses towards family witnessed resuscitation in an accident and emergency unit and to make recommendations towards the development of a family witnessed resuscitation protocol based on the results of the first objective. Design: Descriptive quantitative research design. The population was comprised of accident and emergency nurses who all met the inclusion criteria, with a sample size of n=76. Methods: South African Accident and Emergency nurses completed a self-administered questionnaire which was aimed at determining their experiences and attitudes towards family witnessed resuscitation. The questionnaire was divided into four sections. The first section was demographic data, the second section investigated nurses experiences on family witnessed resuscitation, the third section further examined the nurses attitudes of family witnessed resuscitation, which comprised 5 point Likert Scale questions ranging from strongly agree to strongly disagree. An open-ended question was also added (section 4) to allow nurses to expand upon their experiences and attitudes towards family witnessed resuscitation. Results: Of the total sample (n=76), the majority (67.1%; n=49) of respondents reported that they had not experienced a situation in which family members were present during resuscitation. In addition, only six (n=6; 8.0%) respondents had offered the family an opportunity to be present at the bedside during resuscitation and 55.4% (n=42) reported that family members had not requested to be present during CPR. Most (86.5%; n=64) of the respondents reported that there was no written policy or protocol regarding family presence during resuscitation in the two academic hospitals. An overwhelming (86.8%; n=66) of the respondents believed the family members should not be offered the opportunity to be present during CPR. Furthermore 77.6% (n=59) of respondents indicated that family presence during CPR was not common practice, 77.6% (n=59) did not find family presence beneficial for the patient. When asked whether family members might decide to stop CPR, the majority (88.2%) of respondents disagreed and 11.8% agreed. Upon unsuccessful CPR, 65.8% (n=50) of nurses believed being present would not help the family members grieving process and 46.1% (n=35) were concerned that their emotional readjustment would be prolonged. Conclusion: It can be concluded from the study that accident and emergency nurses of two academic hospitals in the Gauteng Province have not experienced family witnessed resuscitation, furthermore, there were no written policies or protocols regarding family witnessed resuscitation. Relevance to clinical practice: It is recommended that policies or protocols towards family witnessed resuscitation be developed. Furthermore the resuscitation team need to be in- serviced on this internationally recognised practise to promote good patient care delivery in the accident and emergency unit.
A research report is submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2015